Pengaruh Pemberian Ekstrak Alga Merah (gracilaria verrucosa) terhadap Aktivitas SGPT pada Tikus Putih (rattus norvegicus) Jantan Galur Wistar yang Diinduksi Parasetamol Dosis Tinggi - Fikri, Akbar Maharudin; Tehupuring, Sihning EJ (Universitas Wijaya Kusuma Surabaya, 2018)
Background: Administration of high dose paracetamol may increase the metabolic pathways that produce N-acetyl-p-benzoquinonimin (NAPQI). NAPQI is a reactive substance, resulting liver tissue damage and increase SGPT activity. Red algae extract contains flavonoids that act as antioxidants.Objectives: This research aimed to determine the effect of red algae (Gracilaria verrucosa) extract to the activity of serum glutamic pyruvic transaminase (SGPT) in male Wistar rats (Rattus norvegicus) induced by high dose paracetamol.Methodology: This research used 24 animal of Male Wistar rats. These rats were divided into 3 groups: 1) group of rats fed with standard food; 2) group of rats given paracetamol 1750 mg/kg on day 10; and 3) group of rats given red algae extract 200 mg/kg/day on day 1-11 and paracetamol 1750mg/kg on day 10. On day 11, all rats were sacrificed and SGPT activities were measured by spectrophotometry method.Result: Mann-Whitney test results showed significant difference (p = 0.021) between SGPT activity of group of rats fed with standard food (=81.95±10.103 U/L) and group of rats induced by high dose paracetamol (=97.06±11.19 U/L). Furthermore, there was significant difference (p = 0.016) between SGPT activity of group of rats induced by high dose paracetamol (=97.06±11.19 U/L) and group of rats induced by high doses of paracetamol and fed with red algae extract (=82.73±11.233 U/L).Conclusion: The conclusion of this research showed that high dose paracetamol significantly increased SGPT activity and red algae extract significantly decreased SGPT activity because it contains flavonoids that act as antioxidants.